Idiopathic Constrictive Pericarditis and Eggshell Calcification of the Heart - Vijayvergiya, Rajesh (JACC Case Rep, 2020)
Extensive pericardial calcification is rare in patients with chronic constrictive pericarditis (CCP). We report the case of a young man who had CCP with “eggshell” calcification of the pericardium and the classic features of CCP on echocardiography and cardiac catheterization. The patient had an uneventful recovery following surgical pericardiectomy. (Level of Difficulty: Intermediate.)